Compressive strength performance of OPS lightweight aggregate concrete containing coal bottom ash as partial fine aggregate replacement - Khairunisa, Muthusamy; Mohamad Hafizuddin, Rasid; Fadzil, Mat Yahaya; Mohd Arif, Sulaiman; Sharifah Maszura, Syed Mohsin; Nurul Nadrah Aqilah, Tukimat; Roslina, Omar; Chin, Siew Choo (IOP Publishing, 2018)

(untitled)
Concerns regarding the negative impact towards environment due to the increasing use of natural sand in construction industry and dumping of industrial solid wastes namely coal bottom ash (CBA) and oil palm shell (OPS) has resulted in the development of environmental friendly lightweight concrete. The present study investigates the effect of coal bottom ash as partial fine aggregate replacement towards workability and compressive strength of oil palm shell lightweight aggregate concrete (OPS LWAC). The fresh and mechanical properties of this concrete containing various percentage of coal bottom ash as partial fine aggregate replacement were investigated. The result was compared to OPS LWAC with 100 % sand as a control specimen. The concrete workability investigated by conducting slump test. All specimens were cast in form of cubes and water cured until the testing age. The compressive strength test was carried out at 7 and 28 days. The finding shows that integration of coal bottom ash at suitable proportion enhances the strength of oil palm shell lightweight aggregate concrete.